Low-Intensity Light-Responsive Anticancer Activity of Platinum(II) Complex Nanocolloids on 2D and 3D In Vitro Cancer Cell Model. (23rd April 2022) - Vergaro, Viviana; Baldassarre, Francesca; De Castro, Federica; Migoni, Danilo; Dell'Anna, Maria Michela; Mastrorilli, Piero; Fanizzi, Francesco Paolo; Ciccarella, Giuseppe
Abstract : This study aimed to evaluate the therapeutic efficacy of low-intensity visible light responsive nanocolloids of a Pt-based drug using a 2D and three-dimensional (3D) in vitro cancer cell model. Biocompatible and biodegradable polymeric nanocolloids, obtained using the ultrasonication method coupled with Layer by Layer technology, were characterized in terms of size (100 ± 20 nm), physical stability, drug loading (78%), and photoactivation through spectroscopy studies. The in vitro biological effects were assessed in terms of efficacy, apoptosis induction, and DNA-Pt adducts formation. Biological experiments were performed both in dark and under visible light irradiation conditions, exploiting the complex photochemical properties. The light-stimuli responsive nanoformulation gave a significant enhancement in drug bioactivity. This allowed us to achieve satisfying results by using nanomolar drug concentration (50 nM), which was ineffective in darkness condition. Furthermore, our nanocolloids were validated in 3D in vitro spheroids using confocal microscopy and cytofluorimetric assay to compare their behavior on culture in 2D monolayers. The obtained results confirmed that these nanocolloids are promising tools for delivering Pt-based drugs.